2007
DOI: 10.1136/qshc.2006.019349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an intervention aimed at improving voluntary incident reporting in hospitals

Abstract: Objectives: To assess the effectiveness of an intervention package comprising intense education, a range of reporting options, changes in report management and enhanced feedback, in order to improve incidentreporting rates and change the types of incidents reported. Design, setting and participants: Non-equivalent group controlled clinical trial involving medical and nursing staff working in 10 intervention and 10 control units in four major cities and two regional hospitals in South Australia. Main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 17 publications
6
86
0
1
Order By: Relevance
“…21 A previous initiative to address some of these issues significantly increased the number of occurrence reports submitted over a variety of hospitals and units. 29 Acute care centres in Canada that wish to increase incident reporting may achieve a comparable increase through similar programming.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 A previous initiative to address some of these issues significantly increased the number of occurrence reports submitted over a variety of hospitals and units. 29 Acute care centres in Canada that wish to increase incident reporting may achieve a comparable increase through similar programming.…”
mentioning
confidence: 99%
“…In previous surveys, reasons for under-reporting among health care providers were uncertainty about what should be reported and who should do the reporting, as well as concerns about implicating colleagues, legal ramifications, and time constraints. 21,29 Health care providers reported that they would be more likely to submit occurrence reports if they could receive regular feedback about the reported incidents and if they believed or witnessed that occurrence reporting changed patient care and system processes. 30 These providers would also be more likely to report if they could submit in an electronic format or if they were to receive further education to help determine what type of incident requires a report.…”
mentioning
confidence: 99%
“…Second, despite a corporate policy on what and how to report safety events, an explanation of how corporate safety interventions or strategies are linked to individual accountability for safe care in daily work is recommended. Key to these efforts are including personal stories, using reminders, and making content relevant and user friendly for all intended audiences [4,13] . In turn, this should assist with embedding error wisdom [35] and reciprocal accountability [32][33][34] whereby there is a clear idea of what safety events are to be reported and acted on.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the hospital's corporate safety plan, a multi-pronged approach to improving event reporting and safety culture was developed using recommendations from national organizations [11,12] and empirical work demonstrating the effectiveness of interventions (e.g. education and training, publications and newsletters, incentives and rewards to report safety events, and online networks) [1,[5][6][7][12][13][14][15][16] . SafetyNET was developed with a team of researchers, administrators, clinicians, and educators with expertise in patient safety and quality improvement.…”
Section: Intervention Description-safetynetmentioning
confidence: 99%
“…Multimodal interventions may be required to promote behavioural change, particularly in areas such as emotions, a complex process that takes place over time at individual, population and organisational levels. Evans et al reported the evaluation of an intervention aimed at improving voluntary incident reporting in hospitals [23]. The intervention comprised providing intense education, a range of reporting options, changes in report management and enhanced feedback.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%